Evaluation of a Periodic Multiphasic Health Checkup - Dales, L. G.; Friedman, G. D.; Collen, M. F. (Methods of Information in Medicine, 1974)
A controlled trial aimed at testing the efficacy of periodic Multiphasic Health Checkups in preventing or postponing morbidity, disability, and death has been in progress since 1964. After seven years of follow-up the most striking findings are: 1) a reduction in self-reported disability among men aged 45—54 at entry who were urged to take the periodic checkups; and 2) in the urged group as a whole, a reduction in mortality from a collection of causes deemed beforehand to be potentially postponable through use of periodic checkups. There are no strong indications that chance fluctuation, selective loss to follow-up, selective under-reporting, or initial health status discrepancies can explain the mortality difference.
Keywords: Periodic Health Checkups; Multiphasic Screening; Automated Multiphasic Health Testing; Preventive Medicine Evaluation